Comparative study of In-process and finished products quality control test for tablet and capsules according to pharmacopoeias - Chavan, Harishchandra; Chhabra, Gurmeet; Gujarathi, Nayan; Jadhav, Anil (Asian Journal of Pharmaceutical Research and Development, 2018)
The goal of all Pharmaceutical industry is to make a good quality product and for this it is necessary to allow In-Process Quality Control (IPQC) Approaches. In-process quality control tests are done before the manufacturing process is completed. The function of in-process controls is to monitor and if necessary, adaptation of the manufacturing process to achieve the required specification. This may incorporate control of equipment and environment too. In-process materials should be tested for their physical parameters and its quality attributes which are later approved or rejected by the quality control department. The reason of IPQC is to deliver a cumulative finished product by avoiding or eliminating mistakes at every stage in production. The objective of this study is the comparison of In-process quality control test of India Pharmacopoeia, British Pharmacopoeia and the United state Pharmacopoeia. It was observed from various studies that quality control tests for tablet and capsule listed in different pharmacopoeias have slight similarities and differences